THE IMPACT OF SOCIAL MEDIA ON THE IMPACT OF SOCIAL MEDIA ON THE FOUR COMPONENTS OF ENGLISH LANGUAGE DEVELOPMENT FOR LEARNERS (A CASE STUDY) - Torchinava , Ekaterina (Online Journal of Humanities ETAGTSU, 2023)
The role of social media in the development of the four components of language (listening, speaking, reading and writing) has been a topic of interest for researchers and teachers. The research described in this paper reveals that the utilization of social media and online platforms, alongside digital interactions and communication among peers, yields exceptional outcomes in the development of English language skills among children. Furthermore, it also underscores the significant role of these contemporary tools in fostering accurate grammatical usage and improving reading skills by providing access to a wide range of authentic texts and real-world examples. The research also proposes that social media can promote writing skills by providing a platform for writing and sharing ideas with others. In general, social media can play a crucial role in the development of all four components of the English language and can be a valuable tool for language learners and teachers. Full Text (PDF)